Aspects of Fraud Prevention in The National Health Insurance Program in Bengkulu Province, Indonesia: A Realist Evaluation (Universitas Muhammadiyah Yogyakarta, 2025)
Fraud in Indonesia’s National Health Insurance (JKN) program threatens the integrity and sustainability of the national health system. Although there have been anti-fraud regulations, their implementation varies across institutional levels. This study aims to identify and evaluate evaluate the mechanisms and contextual factors influencing the implementation of anti-fraud policies at healthcare facilities in Bengkulu Province. Conducted between 2018 and 2019, this realist evaluation involved purposively selected hospitals and primary health centers with experience in fraud prevention. Data were collected through in-depth semi-structured interviews with twelve key informants, including hospital directors, provincial and district health officials, members of anti-fraud teams, and representatives of BPJS Health, supported by policy document reviews. Thematic analysis using the Context–Mechanism–Outcome (CMO) framework identified three key challenges. At the provincial level, anti-fraud teams were not established due to perceived overlap with clinical governance roles. At the district/city level, teams functioned administratively with limited authority and technical capacity. At the hospital level, internal audit initiatives improved claim verification but faced obstacles in coordination, training, and communication constraints with BPJS Health. Additional vulnerabilities included limited access of specialists, strict referral pathways, and frequent claim code mismatches, all of which increased fraud risk. The findings highlight the importance of clrear role differentiation for anti-fraud actors, stronger audit systems, and imporved collaboration and communication between health facilities and BPJS Health. Continuous technical education and context-adapte policies are considered vital for effective fraud prevention. The study provides practical guidance for enhancing the design and implementation of anti-fraud policies in the JKN program and a short time frame. Future research should broaden the geogrhaphic scope and extend the duration, while exploring digital and inncovative approaches for anti-fraud measures.